Morfofisiologia e valor nutritivo de gramineas forrageiras Tropicais sob fontes e doses de fósforo - Santos, Ívina Paula Almeida dos (2004)
The objective of this work was to study morphophysiology and nutritive value of tropical forage grasses, at 35 days of regrowth, under sources and doses of P an one experiment was driven in the field in area of the Department of Animal Science of the Universidade Federal de Lavras - UFLA, Lavras, MG. The experimental design used was a randomized complete block, in split split plot scheme, with three repetitions, being allocated in the plot the grasses (coastcross bermudagrass, florona stargrass and kikuyu grass), in the subplot the sources of P (TS-Triple superphosphate; RF- Reactive phosphate, Arad/Onk Djebel and NP- Nature phosphate, Araxa) and, in the subsubplot, the doses of P (0, 40, 80 and 120 kg/ha of P2O5). The coastcross bermudagrass and florona stargrass presented larger tillers density (TD) than the kikuyu grass, provided by RP and NP. However, in this last one and in the coastcross bermudagrass less heavy tillers were observed. The tillers weigth (TW) of the coastcross bermudagrass didn't vary with the phosphorus fertilization, however TS and RP provided tillers more weighted for the florona stargrass and, for kikuyu grass, RP and NP. Variables as total number of leaves (TNL), number of lives leaves (NLL), number of deads leaves (NDL), leaf final length (LFL), elongation duration (ED), leaf elongation rate (LER), leaf appearance rate (LAR) and phyllochron (PHYL) were not influenced (P>0.05) for the phosphorus fertilization that, on the other hand, affected number of emergents leaves (NEL). The grasses didn't vary with relationship to TNL, NLL, LAR and PHYL, presented medium values of 10.52 and 8.25 leaves/tiller; 0,40 leaves/day and 2,53 days/leaf, respectively; the florona stargrass showed larger LER, 9.04 mm/day. The kikuyu grass was higher in NEL (3.37), NDL (2.87), LFL (11.03 cm) and ED (17.16 days). Also, it was verified that the ED of individual leaves increase with the insert level of them in detriment of LAR. The kikuyu grass presented larger leaf area ratio (LAR), leaf weigth ratio (LWR), specific leaf area (SLA), leaf area per plant (PLA) and leaf:stem ratio (LSR) than the coastcross bermudagrass and the florona stargrass that were shown more similar to each other, being observed medium values of two years for the kikuyu grass of 0.0218 m2/g, 0.4985 g/g, 0.0482 m2/g, 0,0034 m2 and 1.71, respectively. The yield of the coastcross bermudagrass in the wet and dry seasons was higher (P <0.05) than the florona stargrass and kikuyu grass, with medium productions of two years equal to 12.7 and 4.7, 11.2 and 2.9 and 6.33 and 3.73 t/ha, respectively. However, the kikuyu grass presented better nutritive value. It was observed that 70-80% of the yield of DM of the grasses occurred in the wet season (october/march). The TS provided higher (P<0.01) production of DM of the grasses, however not very higher that of the RF and NF, being observed values of the average of two years of 13.6, 13.3 and 12.8 t/ha, respectively. In the general, the phosphorus fertilization didn't affect the contents of NDF, ADF and IVDMD of the grasses; even so, it increased (P<0.05) the contents of N, P, Ca and Mg. The kikuyu grass presented higher (P <0.01) concentration of inorganic P (322 µg/g) than that the coastcross bermudagrass (244 µg/g) and the florona stargrass (235 µg/g). However, the coastcross bermudagrass presented larger concentration of total P than that the florona stargrass and kikuyu grass, being observed values of 589,442 and 492 µg/g, respectively.